Pokemon Phenomenon and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
A survey by questionnaire of 67 Japanese children affected by watching the animated television series Pocket Monsters (Pokemon) on December 16, 1997 and their parents was compared with that of children not affected by the program, in a study conducted at Showa University School of Medicine, Tokyo, Japan, and other centers.